Selection and application of bacteria for bioclogging of sandy soil - Tan, Wei Wei. (2009)
Conventional technologies, such as permeate and chemical grouting, are still lacking in providing an environmental safe and cost effective option for large-scale construction of reservoirs. Hence there calls for more novel technologies which involve indigenous soil microorganisms to modify the soil for an environmental safer option. Bioclogging using slime producing bacteria had been studied to reduce permeability of sand by 4 x 10-3 times over 30 days. Slime producing and oligotrophic bacterium, Caulobacter crescentus, also showed the strongest adhesive strength measured for microbial attachment, which could be tapped on to bind the loose sand particles together. Microbial biocementation using calcium/urea solution and Bacillus pasteurii cells in loose sand core could produce cement that had strength of 0.05 – 5 MPa.